Long-term live-cell imaging approaches to study lateral root formation in Arabidopsis thaliana. (23rd November 2018) - Goh, Tatsuaki
Abstract : Observing cellular and molecular processes for an extended time at various scales are crucial for understanding biological processes during organogenesis. This review focuses on the contribution of multi-scale imaging approaches to understanding plant lateral root formation processes from cells to organs. Abstract: Lateral roots comprise the majority of the branching root system and are important for acquiring nutrients and water from soil in addition to providing anchorage. Lateral roots develop post-embryonically from existing root parts and originate from a subset of specified pericycle cells (lateral root founder cells) located deep inside roots. Small numbers of these specified pericycle cells undergo several rounds of cell division to create a dome-shaped primordium, which eventually organizes a meristem, an essential region for plant growth with active cell division, and emerges from its parental root as a lateral root. Observing cellular and molecular processes for an extended time at various scales are crucial for understanding biological processes during organogenesis. Lateral root formation is an example of the successful application of live-cell imaging approaches to understand various aspects of developmental events in plants, including cell fate determination, cell proliferation, cell-to-cell interaction and cell wall modification. Here I review the recent progress in understanding the molecular mechanisms of lateral root formation and the contribution of live-cell imaging approaches.